Bacterial programming of host responses: coordination between type I interferon and cell death - Dhariwala, Miqdad O.; Anderson, Deborah M. (Frontiers in Microbiology, 2014)
During mammalian infection, bacteria induce cell death from an extracellular or intracellular niche that can protect or hurt the host. Data is accumulating that associate type I interferon (IFN) signaling activated by intracellular bacteria with programmed death of immune effector cells and enhanced virulence. Multiple pathways leading to IFN-dependent host cell death have been described, and in some cases it is becoming clear how these mechanisms contribute to virulence. Yet common mechanisms of IFN-enhanced bacterial pathogenesis are not obvious and no specific interferon stimulated genes have yet been identified that cause sensitivity to pathogen-induced cell death. In this review, we will summarize some bacterial infections caused by facultative intracellular pathogens and what is known about how type I IFN signaling may promote the replication of extracellular bacteria rather than stimulate protection. Each of these pathogens can survive phagocytosis but their intracellular life cycles are very different, they express distinct virulence factors and trigger different pathways of immune activation and crosstalk. These differences likely lead to widely varying amounts of type I IFN expression and a different inflammatory environment, but these may not be important to the pathologic effects on the host. Instead, each pathogen induces programmed cell death of key immune cells that have been sensitized by the activation of the type I IFN response. We will discuss how IFN-dependent host cell death may increase host susceptibility and try to understand common pathways of pathogenesis that lead to IFN-enhanced bacterial virulence.